Reduced connectivity and inter-hemispheric symmetry of the sensory system in a rat model of vulnerability to developing depression - Ben-Shimol, E.; Vollmayr, Barbara; Sartorius, Alexander (Neuroscience, 2015)
Defining the markers corresponding to a high risk of developing depression in humans would have major clinical significance; however, few studies have been conducted since they are not only complex but also require homogeneous groups. This study compared congenital learned helpless (cLH) rats, selectively bred for high stress sensitivity and learned helplessness (LH) behavior, to congenital non-learned helpless (cNLH) rats that were bred for resistance to uncontrollable stress. Naïve cLH rats show some depression-like behavior but full LH behavior need additional stress, making this model ideal for studying vulnerability to depression. Resting-state functional connectivity obtained from seed correlation analysis was calculated for multiple regions that were selected by anatomy AND by a data-driven approach, independently. Significance was determined by t-statistic AND by permutation analysis, independently. A significant reduction in functional connectivity was observed by both analyses in the cLH rats in the sensory, motor, cingulate, infralimbic, accumbens and the raphe nucleus. These reductions corresponded primarily to reduced inter-hemispheric connectivity. The main reduction however was in the sensory system. It is argued that reduced connectivity and inter-hemispheric connectivity of the sensory system reflects an internal convergence state which may precede other depressive symptomatology and therefore could be used as markers for vulnerability to the development of depression.
Gesehen am 31.08.2017